Information Retrieval Technology 8th Asia Information Retrieval Societies Conference, AIRS 2012, Tianjin, China, December 17-19, 2012. Proceedings - Hou, Yuexian; Nie, Jian-Yun.; Sun, Le.; Wang, Bo.; Zhang, Peng.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 8th Information Retrieval Societies Conference, AIRS 2012, held in Tianjin, China, in December 2012. The 22 full papers and 26 poster presentations included in this volume were carefully reviewed and selected from 77 submissions. They are organized in topical sections named: IR models; evaluation and user studies; NLP for IR; machine learning and data mining; social media; IR applications; multimedia IT and indexing; collaborative and federated search; and the poster session.
Session 1: IR Models -- Exploring and Exploiting Proximity Statistic for Information Retrieval Model -- A Category-integrated Language Model for Question Retrieval in Community Question Answering -- Session 2: Evaluation and User Studies -- The Reusability of a Diversified Search Test Collection -- One Click One Revisited: Enhancing Evaluation Based on Information Units -- A Comparison of Action Transitions in Individual and Collaborative Exploratory Web Search -- Session 3: NLP for IR -- Query-Oriented Keyphrase Extraction -- Using Lexical and Thematic Knowledge for Name Disambiguation -- Sells Out or Piles Up? A Sentiment Autoregressive Model for Predicting Sales Performance -- Session 4: Machine Learning and Data Mining -- Are Human-Input Seeds Good Enough for Entity Set Expansion? Seeds Rewriting by Leveraging Wikipedia Semantic Knowledge -- Combining Modifications to Multinomial Naive Bayes for Text Classification -- Organizing Information on the Web through Agreement-Conflict Relation Classification -- Session 5: Social Media -- Exploiting Twitter for Spiking Query Classification -- Where Are You Settling Down: Geo-locating Twitter Users Based on Tweets and Social Networks -- Detecting Informative Messages Based on User History in Twitter -- Session 6: IR Applications -- A Study on Potential Head Advertisers in Sponsored Search -- Feature Transformation Method Enhanced Vandalism Detection in Wikipedia -- PLIDMiner: A Quality Based Approach for Researcher$1 (Bs Homepage Discovery -- Session 7: Multimedia IR and Indexing -- Exploiting and Exploring Hierarchical Structure in Music Recommendation -- Enhancing Music Information Retrieval by Incorporating Image-Based Local Features -- Yet Another Sorting-Based Solution to the Reassignment of Document Identifiers -- Session 8: Collaborative and Federated Search -- What Snippets Say about Pages in Federated Web Search -- CoFox: A Synchronous Collaborative Browser -- Poster Session -- FISER: An Effective Method for Detecting Interactions between Topic Persons -- Cross-Lingual Knowledge Discovery: Chinese-to-English Article Linking in Wikipedia -- Unified Recommendation and Search in E-Commerce -- Identifying Local Questions in Community Question Answering -- Improving Content-Based Image Retrieval by Identifying Least and Most Correlated Visual Words -- Topical Relevance Model -- Adaptive Data Fusion Methods for Dynamic Search Environments -- NMiner: A System for Finding Related Entities by Mining a Bimodal Network -- Combining Signals for Cross-Lingual Relevance Feedback -- A Conceptual Model for Retrieval of Chinese Frequently Asked Questions in Healthcare -- LDA-Based Topic Formation and Topic-Sentence Reinforcement for Graph-Based Multi-document Summarization -- Query Reformulation Based on User Habits for Query-by-Humming Systems -- Query Expansion Based on User Quality in Folksonomy -- Semantically Enriched Clustered User Interest Profile Built from Users$1 (BTweets -- Adaptive Weighting Approach to Context-Sensitive Retrieval Model -- Effective Keyword-Based XML Retrieval Using the Data-Centric and Document-Centric Features -- Unsupervised Extraction of Popular Product Attributes from Web Sites -- Aggregating Opinions on Hot Topics from Microblog Responses -- Topic Sequence Kernel -- Opening Machine Translation Black Box for Cross-Language Information Retrieval -- Topic Based Author Ranking with Full-Text Citation Analysis -- Vertical Classification of Web Pages for Structured Data Extraction -- Grid-Based Interaction for Exploratory Search -- Analyzing the Spatiotemporal Effects on Detection of Rain Event Duration -- Outpatient Department Recommendation Based on Medical Summaries -- Actively Mining Search Logs for Diverse Tags.s
Keywords: Computer science; Data structures (Computer science).; Computer software; Information storage and retrieval systems; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Data Structures; Data Storage Representation; Probability and Statistics in Computer Science